Room for improvement in pulmonary capillary wedge pressure reporting: a review of hemodynamic tracings at a large academic medical center. (November 2020) - Johnson, Shelsey W.; Witkin, Alison; Rodriguez-Lopez, Josanna; Channick, Richard
To describe the frequency with which pulmonary capillary wedge pressure measurements, obtained during right heart catheterization, are falsely elevated and to educate operators on techniques to improve accuracy of pulmonary capillary wedge pressure reporting. Failure to completely occlude pulmonary artery branch vessels during balloon inflation can lead to falsely elevated, "incomplete" pulmonary capillary wedge pressures. Balloon deflation prior to catheter retraction may result in catheter advancement into smaller branch vessels, yielding an inadvertent but more accurate alternative pulmonary capillary wedge pressure. We hypothesized that this phenomenon can be identified on retrospective review of right heart catheterization tracings, which occurs commonly and goes unrecognized by operators. We conducted a retrospective study of patients undergoing right heart catheterization or right heart catheterization and left heart catheterization with computer-generated pulmonary capillary wedge pressure ≥20 from January 2015 to June 2017. Alternative pulmonary capillary wedge pressures were defined as a pulmonary capillary wedge pressure trace during balloon deflation ≥3 mmHg lower than the reported pulmonary capillary wedge pressure. Inter-rater reliability of tracing reviewers was also evaluated. Results showed that, of the 182 tracings reviewed, an alternative pulmonary capillary wedge pressure was identified in 26 or 14.3% of cases. Eleven of these alternative pulmonary capillary wedge pressures were ≤15 mmHg with a calculated pulmonary vascular resistance ≥3 Wood units in 10 patients, re-classifying the etiology of pulmonary hypertension from post-capillary to pre-capillary in 38.5% of cases. For the eight patients for whom left heart catheterization data were available, left ventricular end-diastolic pressure aligned with the alternative pulmonary capillary wedge pressure. In conclusion, inadvertently obtained, but likely more accurate, alternative pulmonary capillary wedge pressures were identified in almost 15% of procedures reviewed from a busy academic institution. As wedge pressures often drive diagnosis and treatment decisions for patients with cardiac and pulmonary pathology, operators should be attuned to balloon deflation as a time when alternative pulmonary capillary wedge pressures may be identified as they are likely more reflective of left ventricular end-diastolic pressure. Additional tools to ensure accuracy of pulmonary capillary wedge pressure reporting are reviewed.